Design of concrete structures for retaining aqueous liquids design tables to BS 8007 - Cheng, Richard (Thomas Telford ; American Society of Civil Engineers, Publications Sales Dept. [distributor], 1996)
Offers design tables that assist the design process and save time. This book provides calculations of minimum reinforcement, crack spacing, and crack widths in relation to temperature and moisture effects. It also provides calculations of crack widths in mature concrete under structural loading.